2012
DOI: 10.1007/s11136-012-0289-1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of health-related quality of life in people with Parkinson’s disease: a path analysis

Abstract: Health-related quality of life in PD is associated with self-care limitations, mobility limitations, self-reported history of falls and disease duration. Understanding how these factors are inter-related may assist clinicians focus their assessments and develop strategies that aim to minimize the negative functional and social sequelae of this debilitating disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
95
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 43 publications
5
95
3
Order By: Relevance
“…Additionally, GABS scores had good correlations with measures of balance, disease severity, and functional independence. Th ese results are consonant with the view that balance and gait disturbances are strongly associated with disability and poor quality of life in patients with mild to moderate PD 8 . Balance defi cits and falls are frequent clinical problems in patients with PD 5,22 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Additionally, GABS scores had good correlations with measures of balance, disease severity, and functional independence. Th ese results are consonant with the view that balance and gait disturbances are strongly associated with disability and poor quality of life in patients with mild to moderate PD 8 . Balance defi cits and falls are frequent clinical problems in patients with PD 5,22 .…”
Section: Discussionsupporting
confidence: 85%
“…In the long term, most of the survivors experience falls and around 1/3 sustain fractures 6 . Gait and balance difficulties significantly affect the quality of life of patients with PD, and frequent falls are associated with greater disease severity and increased caregiver burden 5,7,8 . In this scenario, the analysis of balance and gait in patients with PD is an essential step in the context of the clinical evaluation.…”
mentioning
confidence: 99%
“…Structural equation modeling was used to evaluate the fit of the final model by examining a number of statistics. To examine the magnitude of the discrepancy between the sample and fitted covariance matrices, the χ 2 test was used when a nonsignificant test indicated that the model and data were consistent [22] . The comparative fit index examines the difference in overall fit among the models, and values >0.95 indicate a good model fit.…”
Section: Discussionmentioning
confidence: 99%
“…The comparative fit index examines the difference in overall fit among the models, and values >0.95 indicate a good model fit. The root mean square error of approximation evaluates the approximate fit of the model, with values <0.005 suggesting a reasonable goodness of fit [22] . Table 1 presents the clinical characteristics and serum adipokine levels of the patients with CU classified into the responsive and refractory groups, as well as the healthy controls (controls).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced participation is a risk factor for lower QOL post-stroke and in PD [11][12][13], and is associated with increased incidence of depression [14][15][16].…”
Section: Introductionmentioning
confidence: 99%